"No more credit score": Employer credit check bans and signal substitution - Robert Clifford; Daniel Shoag (Federal Reserve Bank of Boston, 2016)
In the past decade, most states have banned or considered banning the use of credit checks in hiring decisions, a screening tool that is widely used by employers. Using new Equifax data on employer credit checks, the Federal Reserve Bank of New York Consumer Credit Panel/Equifax data, and the LEHD Origin-Destination Employment data, we show that these bans increased employment of residents in the lowest-credit score census tracts. The largest gains occurred in higher-paying jobs and in the government sector. At the same time, using a large database of job postings, we show that employers increased their demand for other signals of applicants' job performance, like education and experience. On net, the changes induced by these bans generate relatively worse outcomes for those with mid-to-low credit scores, for those under 22 years of age, and for blacks, groups commonly thought to benefit from such legislation.
Keywords: J78; M50; 330